Cost-utility analysis of palonosetron in the antiemetic regimen for cisplatin-containing highly emetogenic chemotherapy in Japan - Munenobu Kashiwa; Ryo Matsushita (BMC, 2019)
Abstract Background An antiemetic triplet regimen of 5-hydrotryptamine-3 receptor antagonist, dexamethasone, and aprepitant is the standard prophylaxis with highly emetogenic chemotherapy (HEC). A randomized phase III trial comparing palonosetron (PALO) versus granisetron (GRA) in the triplet antiemetic regimen (The TRIPLE study) showed the superiority of PALO over GRA for delayed-phase vomiting in patients receiving cisplatin-based HEC. However, economic efficiency evaluations including quality of life have not been done. The present study was a cost-utility analysis of PALO within the Japanese medical insurance system. Methods The data source was the results of the TRIPLE study. A decision tree was constructed to assess the incremental cost-effectiveness ratio (ICER) using quality-adjusted life years (QALYs) and the medical service fees and the drug price for 2018 from the perspective of the payer. A one-way sensitivity analysis and a probabilistic sensitivity analysis (PSA) were performed to assess the robustness of the model. A threshold analysis was performed to determine the cost-effective price of PALO. Results In the base case, the estimated incremental effect of PALO addition was 0.000645 QALYs, the estimated incremental cost was 10,455 JPY (93.21 USD), and the ICER was 16,204,591 JPY QALY (144,465 USD/QALY). In the PSA, the probability of superior cost-effectiveness was 3.64%. In the threshold analysis, the acceptable price of PALO was estimated to be 7,743 JPY (69.03 USD). Conclusions If willingness-to-pay is taken as 5,000,000 JPY/QALY (44,575 USD/QALY), the antiemetic regimen using PALO for cisplatin-containing HEC was not cost-effective at this time. The cost of drugs, with the arrival of inexpensive generic drugs, will make a major contribution to its cost-effectiveness.